Imanensi dan Transendensi Tokoh Perempuan dalam Novel Geni Jora karya Abidah El Khalieqy: Perspektif Feminisme Eksistensialis Simone de Beauvoir - Puja Safitri; Suminto A Sayuti (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This study aims to analyze the manifestations of immanence and transcendence in the female characters of the novel Geni Jora written by Abidah El Khalieqy, using Simone de Beauvoir’s existentialist feminist perspective. The method employed in this study is a qualitative approach using descriptive analysis. The data source used is the novel Geni Jora by Abidah El Khalieqy, while the data collected includes narratives, dialogues, and descriptions related to women’s existence. Data collection was conducted through reading and note-taking, followed by content analysis involving data processing, information presentation, and drawing conclusions. The research findings indicate that the immanent form of the female characters is depicted through women’s subordination, the disregard of intellectual capabilities, restrictions on freedom of movement, control over life choices, and women’s subordinate position within the patriarchal structure. On the other hand, the transcendent form is demonstrated by the courage to challenge the patriarchal structure, maintain one’s identity, resist injustice, reject the objectification of the body, and utilize education as a tool for self-liberation. The results also indicate that the female characters in Geni Jora not only experience various forms of oppression from the patriarchy but also strive to transcend these limitations to assert their existence as free and independent individuals. This study contributes to expanding the exploration of Simone de Beauvoir’s existentialist feminism within the context of Indonesia literature, particulary through an analysis of the dynamich of immanence and transcendence in the female characters of Geni Jora.